1988
DOI: 10.1002/ijc.2910420417
|View full text |Cite
|
Sign up to set email alerts
|

A new immunotoxin built by linking a hemolytic toxin to a monoclonal antibody specific for immature T lymphocytes

Abstract: Hybrid molecules built by conjugation between monoclonal antibodies (MAbs) and toxins are currently being experimentally tested as potential new anti-cancer agents. These immunotoxins have mainly used the plant toxin ricin as the toxic component, which inhibits protein synthesis at the ribosome level. We present an alternative for toxic components using a hemolytic toxin acting at the membrane level, due to its phospholipase activity. The hemolytic toxin (HT), isolated from the sea anemone Stoichactis helianth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 9 publications
1
22
0
1
Order By: Relevance
“…The results shown in Table 1 indicated that RTX-A demonstrated potent cytotoxic activity (IC 50 = 1–5 nM) against human caner cell lines, including HL-60, MDA-MB-231, HeLa, THP-1, and SNU-C4. The active concentrations of RTX-A, 10 −9 M, agree with the values of the cytotoxicity obtained earlier for the α-PFT of the actinoporin family, ranging from 10 −10 to 10 −7 M, according to reviewed data (Alvarez et al, 2009; Avila et al, 1988; Avila et al, 1989; Tejuca et al, 2004). …”
Section: Resultssupporting
confidence: 88%
“…The results shown in Table 1 indicated that RTX-A demonstrated potent cytotoxic activity (IC 50 = 1–5 nM) against human caner cell lines, including HL-60, MDA-MB-231, HeLa, THP-1, and SNU-C4. The active concentrations of RTX-A, 10 −9 M, agree with the values of the cytotoxicity obtained earlier for the α-PFT of the actinoporin family, ranging from 10 −10 to 10 −7 M, according to reviewed data (Alvarez et al, 2009; Avila et al, 1988; Avila et al, 1989; Tejuca et al, 2004). …”
Section: Resultssupporting
confidence: 88%
“…Actinoporins have been used to elucidate cell membrane dynamics and to investigate pharmaceutically relevant biomedical applications [21,22,23,24]. Several residues have been manipulated to identify functionally important regions within the protein [25], revealing an aromatic-rich region that forms the phosphocholine (POC) binding site, with a single amino acid residue (W112 in Equinatoxin II (EqII)) taking on a key role in initiating sphingomyelin recognition and pore formation [11,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Although other membrane-acting toxins have been investigated for their use in immunoconjugates [7] the first efforts involved a hemolytic toxin from the sea anemone Stichodactyla (formerly Stoichactis) helianthus, which was linked to an antibody that recognizes specific Ag expressed on immature T lymphocytes [8] or to a mAb directed against a carcinoembryonic antigen [9]. More recently, another sea anemone cytolysin, equinatoxin II (EqtII) from Actinia equina, was conjugated with promising results to transferrin, which is a major regulator of cellular growth, and a potent mitogen for a variety of tumors [10].…”
Section: Introductionmentioning
confidence: 99%